THE ROLE OF THE SEVENTH DAY ADVENTIST CHURCH IN HELPING ORPHANS IN THEIR ACADEMIC PERFORMANCE IN PRIMARY SCHOOL EDUCATION - Mokua, Milka Kemunto; Ongaga, Rev. William; Nguku, Rev. William (IJRDO- Journal of Educational Research, 2017)
This study was carried out to determine the role of the Seventh-day Adventist church in helpingorphans in their academic performance in primary education in Getembe Division. The keyfindings revealed that orphanhood negatively affects the academic performance of the learnersespecially through lack of concentration in class caused by thinking about their deceased parents.The findings showed that the physical needs of orphans, such as nutrition and healthcare, canoften appear to be the most urgent. But the emotional needs of children who have lost a parentshould not be forgotten. The findings show that Government support is necessary to carry outnecessary legal reforms and to enforce existing mandates concerning property rights, birthregistration and equitable access to education.